2011
DOI: 10.1016/j.joen.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Odontogenic Differentiation of Senescent Dental Mesenchymal Stem Cells Is Associated with Loss of Bmi-1 Expression

Abstract: Introduction Dental mesenchymal stem cells (dMSCs) may differentiate into odontoblast-like cells and form mineralized nodules. In the current study, we investigated the effects of senescence on odontogenic differentiation of dMSCs. Methods dMSCs were serially subcultured until senescence. Telomere lengths and telomerase activities were determined by quantitative PCR. Expression of genes involved in cell proliferation and differentiation, e.g., Bmi-1, p16INK4A, osteocalcin (OC), dentin sialoprotein (DSP), bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 24 publications
8
48
0
Order By: Relevance
“…Previous studies with bone marrow-derived mesenchymal stem cells and dental pulp stem cells showed a progressive and rapid loss of differentiation potentials with prolonged culture [11][12][13][14]25]. We obtained similar results with DFCs.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies with bone marrow-derived mesenchymal stem cells and dental pulp stem cells showed a progressive and rapid loss of differentiation potentials with prolonged culture [11][12][13][14]25]. We obtained similar results with DFCs.…”
Section: Discussionsupporting
confidence: 86%
“…For example, TGF-b2 was found to inhibit the differentiation of DPCs through activation of the ALK/Smad2/3 signal transduction pathway (20). Bmi-1 plays an important role in maintaining the odontogenic differentiation capacity in dental mesenchymal stem cells during senescence (21). Multiple signaling molecules, including BMPs, fibroblast growth factors, Shh, and Wnts, appear to regulate the early steps of tooth morphogenesis, and some transcription factors associated with these pathways have been shown to be required for tooth development (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Upon serial subculture in vitro dMSCs have been shown to develop morphological changes consistent with cellular senescence, losing their spindle shape and exhibiting flattened, enlarged morphology [13]. Although they exhibit a universal morphology, MSCs originate from different tissue sources, and not all cells collected from these tissues are MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The osteogenic/odontoblastic lineage is among the most well characterized found in MSCs, and BMMSCs and dMSCs have been found to express common osteogenic/odontoblastic markers, such as collagen type I, alkaline phosphatase, and bone sialoprotein [11]. Altered gene expression of these markers has been used to investigate adverse effects of senescence in MSCs [13]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation